التدخل لأغراض انسانية وإشكالية المشروعية - حتحوت, نور الدين (revue mofakir, 2018)
If the principle of non-interference in the internal affairs of states forbid states, organizations and international bodies for addressing or discussing these issues; the principle of respect for human rights on the contrary ordering states and international organizations should intervene in order to respect these rights and to preserve them, and if it leads to discuss the internal affairs of States, discuss also the local conditions, and the evaluation of treatment for these states rights and punish those who violate them. This which puts the two principles in case of conflicts and international legitimacy in the actual legal crisis. This what will be discussed in the following requests.